Pengaruh Literasi Keuangan Digital Terhadap Kemahiran Digital Mahasiswa Universitas Binawan - Nur Fitriyani Sahamony (Jurnal Manajemen & Bisnis Digital, 2022)
Abstract: This study aims to analyze the effect of digital financial literacy on the digital skills of Binawan University students. Digital financial literacy refers to an individual's ability to understand, use and access financial information through digital technology, while digital proficiency includes skills in using digital devices, applications and communicating online. This study uses a quantitative approach by collecting data through a survey of students from various disciplines at Binawan University. The results of the study show that there is a positive and significant relationship between digital financial literacy and students' digital proficiency. Students who have a higher level of digital financial literacy tend to have stronger digital skills, including in terms of using digital devices, accessing information via the internet, and online communication skills. These findings provide evidence that digital financial literacy plays an important role in shaping students' digital skills. This research has important implications in the development of education that is relevant to the needs of the digital era. Higher education institutions can integrate digital financial literacy into the curriculum and provide training that supports the development of students' digital skills. By understanding the link between digital financial literacy and digital proficiency, learning approaches can be designed to equip students with the skills needed to face the challenges of an increasingly digitally connected world of work. Key words: Digital financial literacy, Digital skills, Binawan University, Digital technology, Students Abstrak: Penelitian ini bertujuan untuk menganalisis pengaruh literasi keuangan digital terhadap kemahiran digital mahasiswa Universitas Binawan. Literasi keuangan digital merujuk pada kemampuan individu dalam memahami, menggunakan, dan mengakses informasi keuangan melalui teknologi digital, sementara kemahiran digital mencakup keterampilan dalam menggunakan perangkat digital, aplikasi, dan berkomunikasi secara online. Studi ini menggunakan pendekatan kuantitatif dengan mengumpulkan data melalui survei kepada mahasiswa dari berbagai disiplin ilmu di Universitas Binawan. Hasil penelitian menunjukkan adanya hubungan positif dan signifikan antara literasi keuangan digital dan kemahiran digital mahasiswa. Mahasiswa yang memiliki tingkat literasi keuangan digital yang lebih tinggi cenderung memiliki kemahiran digital yang lebih kuat, termasuk dalam hal penggunaan perangkat digital, akses informasi melalui internet, dan keterampilan berkomunikasi online. Temuan ini memberikan bukti bahwa literasi keuangan digital berperan penting dalam membentuk kemahiran digital mahasiswa. Penelitian ini memiliki implikasi penting dalam pengembangan pendidikan yang relevan dengan kebutuhan era digital. Lembaga pendidikan tinggi dapat mengintegrasikan literasi keuangan digital ke dalam kurikulum dan memberikan pelatihan yang mendukung pengembangan kemahiran digital mahasiswa. Dengan memahami keterkaitan antara literasi keuangan digital dan kemahiran digital, pendekatan pembelajaran dapat dirancang untuk membekali mahasiswa dengan keterampilan yang diperlukan untuk menghadapi tantangan dalam dunia kerja yang semakin terhubung secara digital. Kata kunci: Literasi keuangan digital, Kemahiran digital, Universitas Binawan, Teknologi digital, Mahasiswa